Carbapenemase-Producing Non-Glucose-Fermenting Gram-Negative Bacilli in Africa, Pseudomonas aeruginosa and Acinetobacter baumannii: A Systematic Review and Meta-Analysis - Mizan Kindu; Lemma Derseh; Baye Gelaw; Feleke Moges (International Journal of Microbiology)
Background. Studies have reported that the existence of CP bacteria in Africa, but, in general, comprehensive data about the molecular epidemiology of CP organisms are limited. Therefore, this systematic review and meta-analysis expound the pooled prevalence of CP P. aeruginosa and CP A. baumannii clinical isolates in Africa. It also identified the diversity of carbapenemases or their encoding genes among the isolates in Africa. Lastly, the review observed the trends of these CP isolates in Africa. Methods. A comprehensive search was performed between July 2019 and October 2019 in the following databases: PubMed, Google Scholar, and African Journal online. The included articles were published only in English. The screening was done by two authors independently. The data extracted on Excel spreadsheet were transferred to STATA 11 software for analysis. Results. From a total of 1,454 articles searched, 42 articles were eligible. Most of the studies were conducted in the North Africa region. But there was no report from Central Africa. The pooled prevalence of CP P. aeruginosa and CP A. baumannii among the clinical specimens in Africa was 21.36% and 56.97%, respectively. OXA-23 and VIM were the most prevailing carbapenemase among P. aeruginosa and A. baumannii, respectively. The cumulative meta-analysis revealed a relative increment of the prevalence of CP P. aeruginosa over time in Africa but it showed a higher prevalence of CP A. baumannii isolates across years. Conclusion. The review revealed a high pooled prevalence of CP A. baumannii clinical isolates in Africa which needs urgent action. Moreover, the emergence of concomitant carbapenemases, especially OXA-23 +  NDM among CP A. baumannii, was also an alarming problem.